2017
DOI: 10.1016/j.str.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Protein Structure Models from Electron Microscopy

Abstract: Summary An increasing number of biomolecular structures are solved by electron microscopy (EM). However, the quality of structure models determined from EM maps vary substantially. To understand to what extent structure models are supported by information embedded in EM maps, we used two computational structure refinement methods to examine how much structures can be refined using a dataset of 49 maps with accompanying structure models. The extent of structure modification as well as the disagreement between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Density maps that were determined at a resolution between 5.0 Å to 10.0 Å and have an associated atomic structure in PDB were selected. Then, to ensure that a map and its associated structure have sufficient structural agreement, the cross-correlation between the experimental map and the simulated map density at the resolution of the experimental map computed from the structure was examined 34 and only maps with a cross-correlation of over 0.65 were kept. Finally, we computed the sequence identity between underlined proteins in pairs of EM maps, and a map was removed from the dataset if its underlined protein has over 25% identity to a protein of another map in the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Density maps that were determined at a resolution between 5.0 Å to 10.0 Å and have an associated atomic structure in PDB were selected. Then, to ensure that a map and its associated structure have sufficient structural agreement, the cross-correlation between the experimental map and the simulated map density at the resolution of the experimental map computed from the structure was examined 34 and only maps with a cross-correlation of over 0.65 were kept. Finally, we computed the sequence identity between underlined proteins in pairs of EM maps, and a map was removed from the dataset if its underlined protein has over 25% identity to a protein of another map in the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure to vary the weight factor between data and model has been investigated earlier by Monroe et al (2017) in the context of MDFF and Rosetta, where they found that most models could be "refined further", although their dataset was mainly aimed at lower resolution cases down to 20Å. In addition, besides the difference in software platform used, they did not explicitly show how the weight factor relates to the cross correlation or how to decide on the optimal weight factor at high resolution cryo-EM modeling.…”
Section: Re-refining Cryo-em Structures With Phenix / Opls3ementioning
confidence: 99%
“…Out of 44 fragments in the data set, the model by MAINMAST had a lower or identical RMSD with RosettaES models for 16 cases, and better or worse but within an RMSD margin of 0.5 or 1.0 Å to RosettaES models for 26 and 32 cases, respectively. Considering a recent study that investigated variability of structure models from EM maps 29 , a difference within 1 Å is not meaningful for maps determined at a resolution of 3 Å. Thus, overall the performance of MAINMAST was comparable to RosettaES.…”
Section: Resultsmentioning
confidence: 85%